COMPARATIVE ANALYSIS OF PADDY AND OIL PALM FARM INCOME IN TANJUNG JABUNG TIMUR REGENCY - Junita Purba; Dompak Napitupulu; Yusma Damayanti (School of Business, Bogor Agricultural University (SB-IPB), 2019)
This research aims to analyze the cost and net income of wetland paddy and palm oil smallholder farming in Tanjung Jabung Timur Regency. The subjects of this research were rice and oil palm smallholder farmers particularly palm oil farmers who were recorded to perform functional shift of land use such as from rice to palm oil. The primary data obtained through interviews with rice and oil palm smallholder farmers in research areas, and secondary data collected from various offices and related agencies. Data analyzes used quantitative descriptive methods. The results showed that net income of oil palm farming was significantly greater than net income of rice farming per ha per year. A lower income from rice farming activity was caused by a higher production cost due to higher labor costs compared to oil palm farming. Keywords: farm management, rice farming, oil palm, cost, farm income